UJI KUALITATIF ZAT PEWARNA PADA JAJANAN KHAS MINANGKABAU KERIPIK BALADO DI PADANG, SUMATERA BARAT 2017 - Nopriadi Nopriadi (EcoNews, 2019)
Based on recent survey in some location in Padang, it was clearly seen that some of keripik balado have glaring red color and it was seen also that there was a teperation between red substance from the chili with the red sintetic substance used on it. This research ained to know the kind of colored substance used as an editional substance food in producing keripik balado in Padang West Sumatera. This is a descriptive research with used for describing the kind of colored substance in keripik balado producing and marketing in padang city. The research was held on April to November 2017, by checking the sampel in Baristand industry in Padang. The research population was all the producer or the industry of keripik balado in padang city with indicated sample by total sampling. The data collacting system used in this research was primary and secondary data, than those were processing manually referred to Permenkes RI No.772/Menkes/Per/IX/1988 about food additional substances and the frade minister regulation No.4/M-DAG/PER/2/2006 about distribution and controlling of hazardous substances. The result of this research showed that half of tesed sampling used natural substances as the additional colored substance for 20 sampling and the rest for 21 sampling indicated using sintetic colored substance as the additional colored substance as mention 18 samplings using eritrosin, 6 samplings using sunset yellow, and 2 samplings using ponceau 4R, specific sintetic colored substance (Eritrosin, Sunset Yellow, and Ponceau 4R). This colored substance may be used as food sintetic substance with a limitation usage of quantity (sufficient). It is suggested to the next researcher to do the qualitative test to know the quantity of sintetic colored substance used by the producer of keripik balado in order to apoid the health effect .